Farāʾid Alfāẓ An-nābaāt fī al-Qurʾān al-Karīm: Dirāsaẗ fī al-‘iʿjāz al-Luġhowiy Wā At-Tarbiyah Al-Islaamiyah - Elsayed Mohamed Salem Alawadi; Kamal Abdel Aziz Ibrahim; Rijal Mahdi; Irsal Amin (IAIN Padangsidimpuan, 2022)
This research is reveal the secrecy of the plant's sentences in the Qur'an, both specific and general aspects as it has not been previously revealed. This in-depth study in uncovering this uniqueness presents beauty because it is not repeated, and has root words so that it can be seen clearly the beauty of the presentation and arranged according to the context of the study is a clear linguistic system for those who understand. In addition to this linguistic beauty, the usefulness of this study also has meaning from the philosophical aspect of living life which can be used as a life lesson in the form of the value of life. This research is descriptive phenomenological research that uses an integrative approach and linguistic analysis by combining historical methods that explore phenomena both from the aspect of the word origin and the depth of meaning from the philosophical aspect of education. This research consists of two parts, namely the linguistic and philosophical aspects of Islamic education. From the linguistic aspect, there are three studies, namely the definition of linguistic and idiomatic characteristics, critical and rhetorical inheritance, and the uniqueness of plants in the Qur'an. Meanwhile, from the philosophical aspect of education, it is to explore the beauty of God's creation and make it an example in human life that provides many benefits to the surrounding environment. The results of the study conclude that ‎the study of plants in the Qur'an has diverse characteristics which are extremely beautiful in enriching language ‎scholarship and having a philosophical value from the living ways of plants that ‎ give benefits. The Qur'an has many unique characteristics, both historically and in contemporary reality. One of the uniqueness is the linguistic and rhetorical aspects of the word plant. The development of plants that provide many benefits to the surrounding nature can be imitated by humans as intelligent beings.